Students’ Perceptions of Duolingo Mobile Assisted Language Learning (MALL) in Learning English Vocabulary - Geminastiti Sakkir; Nur Aziza Syamsuddin (PT ARRUS Intelektual Indonesia, 2023)
This study aimed to find out the students’ perceptions of Duolingo Mobile Assisted Language Learning (MALL) in learning English vocabulary. This study involved 32 seventh-grade students from SMPN 1 Pangkajene during the academic year 2022/2023. Descriptive quantitative was used to carry out the study. This study's data was analyzed using quantitative data from a questionnaire. The questionnaire consisted of 30 closed-ended questions. The study found that the Duolingo application positively impacted students' language learning, particularly in acquiring new vocabulary. Students are becoming more enthusiastic to learn and are practicing and using their language skills in everyday circumstances. Furthermore, after using the Duolingo app, students' vocabulary and ability to recall it rapidly improve, as do structure and pronunciation, making it easier for students to improve their English language acquisition. Students found the app easy, helpful, and enjoyable for their English language learning practice. They prefer it over traditional book-based homework due to its convenience, accessibility in various formats, especially mobile, and gamification. The application’s success is attributed to its varied prompts skill-interleaving lessons gamification aspects and diverse lesson content perceived by the students.